2012
DOI: 10.1016/j.ajhg.2011.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Gene-Centric Meta-Analysis across 39 Studies Identifies Type 2 Diabetes Loci

Abstract: To identify genetic factors contributing to type 2 diabetes (T2D), we performed large-scale meta-analyses by using a custom ∼50,000 SNP genotyping array (the ITMAT-Broad-CARe array) with ∼2000 candidate genes in 39 multiethnic population-based studies, case-control studies, and clinical trials totaling 17,418 cases and 70,298 controls. First, meta-analysis of 25 studies comprising 14,073 cases and 57,489 controls of European descent confirmed eight established T2D loci at genome-wide significance. In silico fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
167
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 239 publications
(183 citation statements)
references
References 80 publications
12
167
1
1
Order By: Relevance
“…The observed dual role of TM6SF2 in TRL secretion and hepatic TG content is in line with data from population studies demonstrating associations between the 19p12 locus and plasma TG concentration (1-6) and hepatic steatosis (7,8). The clinical importance of this locus is underlined by its relationships to coronary artery disease (5,9,18,19) and type 2 diabetes (10,11). It is expected that further analysis of TM6SF2 will uncover the biological function of TM6SF2 in hepatic lipid metabolism, thereby providing new insights into the complex relationship between liver TG metabolism, coronary artery disease, and type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The observed dual role of TM6SF2 in TRL secretion and hepatic TG content is in line with data from population studies demonstrating associations between the 19p12 locus and plasma TG concentration (1-6) and hepatic steatosis (7,8). The clinical importance of this locus is underlined by its relationships to coronary artery disease (5,9,18,19) and type 2 diabetes (10,11). It is expected that further analysis of TM6SF2 will uncover the biological function of TM6SF2 in hepatic lipid metabolism, thereby providing new insights into the complex relationship between liver TG metabolism, coronary artery disease, and type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 67%
“…The lead SNP (rs10401969) in the 19p12 locus is part of a large linkage block containing 19 expressed genes, none of which has previously been implicated in lipid metabolism. In addition, GWA studies have also found evidence for an association between the 19p12 locus and nonalcoholic fatty liver disease (7,8), coronary heart disease (5, 9), and diabetes mellitus (10,11). Obviously, these conditions pose a considerable challenge for the identification of the functional gene(s) in the 19p12 locus responsible for the observed relationships with different phenotypes.…”
mentioning
confidence: 99%
“…Compared with selected pathways by Perry et al, the WNT signaling pathway was the most significant pathway gene set in both analyses. The WNT signaling contains TCF7L2 which is significantly associated with T2D in GWAS and may influence to T2D by affecting GLP-1 levels [50,51]. Compared with functional modules from SNP combination and functional modules from genome-wide SNPs, focal adhesion, EGFR (ErbB1) signaling pathway, and hemostasis functional modules are enriched in both expanded GSEAs.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 The rs7903146 single-nucleotide polymorphism (SNP), located in intron 3 and the one with the strongest association to T2D risk, has been the most widely studied TCF7L2 variant. Current evidence suggests that rs7903146 may affect risk of T2D through its effects on enhancer activity 3,4 resulting in higher TCF7L2 gene expression.…”
mentioning
confidence: 99%